Pelatihan Kader Posyandu Tentang Pengolahan Makanan Tambahan Berbasis Pangan Lokal Untuk Balita Dan Ibu Hamil - Doloksaribu, Tetty Herta; Herta Masthalina; Nainggolan, Herly (STMIK Royal, 2025)
Abstract: Pregnancy and toddlerhood are crucial periods that determine a child’s future growth and development. In Wonosari Village, the nutritional intake of pregnant women and toddlers is below the recommended dietary allowance. One of the specific nutritional interventions that can be implemented is the provision of supplementary food (PMT) based on local food. This community service activity aimed to improve the knowledge and skills of posyandu cadres regarding the PMT based on local food for toddlers and pregnant women. The program involved training 40 cadres in the working area of Dalu Sepuluh Health Center, Tanjung Morawa District, Deli Serdang Regency, on May 28, 2025. The training consisted of delivering material on the concept of local food-based PMT and hands-on practice in processing supplementary food. Knowledge was evaluated through pre- and post-tests. Skills were evaluated through observation during processing practices. The results indicated an increase in cadres’ knowledge, with the average score rising from 95.4 to 99.4. Skills also improved, particularly in the accuracy of ingredient measurement and appropriate portion determination. These findings imply that local food-based PMT training can enhance the capacity of posyandu cadres and contribute to strengthening community-based efforts in improving maternal and child nutrition. Keywords: cadres; PMT; pregnant women; toddlers Abstrak: Masa kehamilan dan balita merupakan fase penting yang menentukan kualitas tumbuh kembang anak. Di Desa Wonosari, asupan gizi ibu hamil dan balita di bawah angka kecukupan gizi yang dianjurkan, sehingga diperlukan intervensi gizi spesifik melalui PMT berbasis pangan lokal. Kegiatan pengabdian ini bertujuan untuk meningkatkan pengetahuan dan keterampilan kader posyandu mengenai pengolahan makanan tambahan berbasis pangan lokal untuk balita dan ibu hamil. Metode yang digunakan adalah pelatihan dengan sasaran 40 orang kader posyandu di wilayah kerja Puskesmas Dalu Sepuluh, Kecamatan Tanjung Morawa Kabupaten Deli Serdang. Pelatihan dilaksanakan pada 28 Mei 2025, terdiri dari penyampaian materi tentang PMT berbasis pangan lokal dan praktik pengolahan makanan tambahan untuk balita dan ibu hamil. Evaluasi pengetahuan melalui pre-test dan post-test menggunakan kuesioner. Keterampilan dievaluasi dengan observasi pada saat praktik pengolahan. Pelatihan menghasilkan peningkatan skor pengetahuan kader posyandu dari 95,4 menjadi 99,4, dan peningkatan keterampilan tentang ketepatan penggunaan jumlah bahan pangan dan porsi PMT untuk ibu hamil dan balita. Kata kunci: balita; ibu hamil; kader; PMT